Studentsâ Conception About The Period Of A Simple Pendulum - *, Pujayanto (Proceeding of International Conference on Teacher Training and Education, 2016)
This study aims to describe the studentsâ conception of Physics Education Study Program,Â  Teacher Training and Education Faculty, Sebelas Maret University, about the concept of a simple pendulum period, after conducting a basic physics experiment. A simple pendulum consists of a mass (m) that is hanging at the end of a light string. The string is considered ideal, which is massless and can not be stretched. In the laboratory, students investigated the affects of a few different physical variables on the period of a simple pendulum (T). The variables were mass (m), length of the pendulum (L), and the initial angular displacement (Î¸). The results of the study showed that: 1). all students had a right conception about the dependency of a simple pendulum period on the string length, that is, the period of a simple pendulum is proportional to the square root of the string length; 2). all students had a right conception about the dependency of a simple pendulum period on the mass, that is, the period of a simple pendulum is not dependent on the mass; 3). 42% of the students had a wrong conception about the dependency of the period of a simple pendulum on the initial angular displacement, which they concluded that the initial angular displacement Â does not affect the period of a simple pendulum. It is, analytically provable that the period of a simple pendulum depends on the initial angular displacement.Â